Silicon and nitric oxide‐mediated mechanisms of cadmium toxicity alleviation in wheat seedlings. Issue 5 (4th October 2022) - Singh, Swati; Prasad, Sheo Mohan; Sharma, Shivesh; Dubey, Nawal Kishore; Ramawat, Naleeni; Prasad, Rajendra; Singh, Vijay Pratap; Tripathi, Durgesh Kumar; Chauhan, Devendra Kumar
Abstract: The individual impact of silicon (Si) and nitric oxide (NO, as sodium nitroprusside) on metal toxicity in various plant species has been well documented; however, their combined action in the regulation of metal stress has never been tested yet. Therefore, this study investigates the effects of the combined application of Si and NO in the mitigation of Cd toxicity in wheat seedlings. Seedlings grown on Cd has a significantly declined growth due to an increased accumulation of Cd and oxidative stress markers (due to downregulation of antioxidant defense system particularly ascorbate‐glutathione cycle) and a decreased accumulation of NO and Si. Additionally, the altered leaf and root structures resulted into a declined photosynthetic efficiency. However, the addition of Si and NO alone as well as combined significantly alleviated Cd toxicity in wheat seedlings by lowering the accumulation of Cd and oxidative stress markers and improving leaf and root structures, which are collectively responsible for a better photosynthetic rate under Cd toxicity, and hence an improved growth was noticed. Particularly, the application of Si and NO in combination lowered the oxidative stress markers via upregulating the antioxidant defense system (particularly AsA‐GSH cycle) suggesting the increased efficacy of Si + NO against the Cd toxicity in wheat seedlings as compared to their alone treatments.